Eigenvalues of the time—dependent fluid flow problem I - El-Sayed M. Zayed; El-Sayed F. Elshehawey (International Journal of Mathematics and Mathematical Sciences)
The direct and inverse boundary value problems for the linear unsteady viscous fluid flow through a closed conduit of a circular annular cross-section Ω with arbitrary time-dependent pressure gradient under the third boundary conditions have been investigated.